2016
DOI: 10.1590/1982-021620161868716
|View full text |Cite
|
Sign up to set email alerts
|

Validade e confiabilidade da triagem: "teste da linguinha"

Abstract: Purpose: to verify the psychometric properties -validity and reliability -and the sensitivity, specificity and predictive values of the "Neonatal Tongue Screening Test" from the Lingual Frenulum Protocol for Infants. Methods: this is an experimental retrospective study using data from 100 newborns. The infants were assessed within the first 48 hours after birth using the Neonatal Tongue Screening Test, and subsequently assessed at 30 days of life using the Lingual Frenulum Protocol for Infants. The assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
1
38

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 20 publications
3
21
1
38
Order By: Relevance
“…When these conditions are met, the scale is considered internally consistent . Contrary to what was reported by the developers of the NTST, our assessment of its internal consistency showed that this scale is not homogeneous; its overall internal consistency is poor, half of its items do not have a similar item–test correlation, one item presents a lower than recommended item–test correlation (i.e., 0.30), and two items (i.e., lip posture at rest and frenulum thickness) are inversely correlated with the scale formed by all other items…”
Section: Discussioncontrasting
confidence: 99%
“…When these conditions are met, the scale is considered internally consistent . Contrary to what was reported by the developers of the NTST, our assessment of its internal consistency showed that this scale is not homogeneous; its overall internal consistency is poor, half of its items do not have a similar item–test correlation, one item presents a lower than recommended item–test correlation (i.e., 0.30), and two items (i.e., lip posture at rest and frenulum thickness) are inversely correlated with the scale formed by all other items…”
Section: Discussioncontrasting
confidence: 99%
“…These findings demonstrated that tongue elevation is the position that allows for the best observation of the shape of the tip of the tongue, being possible to identify, more accurately, the presence of V-shaped or heart-shaped tip in subjects with ankyloglossia. Thus, those findings agree with proposals of most assessment tools 5,6,8,[12][13][14][17][18][19][20][21][22][31][32][33] .…”
Section: Discussionsupporting
confidence: 87%
“…Several lingual frenulum assessment tools for infants, children, adolescents, and adults have been published by professionals, such as dentists, lactation consultants, midwives, speech-language pathologists [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• we were not able to find any differences between the versions of the NTst printed in the LFPI Manual 16 and in the paper published by Martinelli et al in 2016. 2 According to Dr. Martinelli's letter, we should have used the latter because this would be the validated version of the instrument published in 2014. Ironically, the Law establishing the mandatory screening of Brazilian newborns for ankyloglossia using the NTst was passed in 2014.…”
mentioning
confidence: 99%